Five sisters the Langhornes of Virginia - Fox, James 1945- (Simon & Schuster, 2000)
A biography of Lizzie, Irene, Nancy, Phyllis, and Nora Langhorne, daughters of a Virginia railroad man, who became prominent figures in high society from the end of the Civil War through the Second World War.
Keywords: Astor, Nancy Witcher Langhorne Astor <Viscountess, 1879-1964>; Brand, Phyllis <1880-1937>; Langhorne family; Langhorne -- Familie; Astor, Nancy W. -- 1879-1964; Geschichte 1900-2000; Geschichte 1865-1945; Alltag, Brauchtum; Americans -- Great Britain -- Biography; Tochter; Großbritannien; USA; Great Britain -- Biography; Great Britain -- Social life and customs -- 20th century; United States -- Social life and customs -- 20th century; Virginia -- Biography; Virginia; Biografie